KEMAMPUAN PEMECAHAN MASALAH SISWA DENGAN PENERAPAN MODELING INSTRUCTION PADA KONSEP LISTRIK DINAMIS - Wahyuni, Sry Wahyuni; Irianti, Mitri Irianti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research aims to describe the problem solving skill of student in class X-7 SMA Negeri 5 Pekanbaru with the implementation of Modeling Instruction in lesson dynamic electric. The research used pre-experimental with one-shot case study design.The subjects were students of class X-7 totalling 39 students, consisting of 16 male students and 23 female students. The instrument of data collection in this study is the problem solving ability test consists of 5 essay questions. Analysis of the data in this study is a descriptive analysis to see an overview of the problem solving skill of student by using the criteria of the level of problem solving skills . The research showed the problem solving skill of student in class X-7 SMA Negeri 5 Pekanbaru with the implementation of Modeling Instruction in lesson dynamic electric are at a medium level (67,46%). Therefore in teaching physics, by using Modeling Instruction could train problem solving skill of student. Key Words : Modeling Instruction, Problem Solving Skill, Dynamic Electric